2023
DOI: 10.1590/1519-6984.249847
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of economic loss caused by Indian crested porcupine (Hystrix indica) in agricultural land of district Muzaffarabad, Azad Jammu and Kashmir, Pakistan

Abstract: The Indian crested porcupine (Hystrix indica) is a vertebrate pest of agricultural lands and forest. The study was aimed to report the damage to local crops by the Indian crested porcupine (Hystrix indica) in the Muzaffarabad District. A survey was conducted to identify the porcupine-affected areas and assess the crop damage to the local farmers in district Muzaffarabad Azad Jammu and Kashmir (AJK) from May 2017 to October 2017. Around 19 villages were surveyed, and a sum of 191 semi-structured questionnaires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Studies on the impact of agricultural grazing methods on pastures show that the harmful dynamic influence of farm animals on soil density tends to become more severe as the grazing load per unit area and grazing intensity increase [82]. Our study found the density of pasture soil to increase to 1.40 g/cm 3 , or by 14.75%, compared to control (no grazing) and the soil to reach 3rd degree degradation by density increase in the variant of intensive agricultural grazing [83].…”
Section: Soil Quality Depending On the Methods Of Agricultural Grazin...mentioning
confidence: 53%
“…Studies on the impact of agricultural grazing methods on pastures show that the harmful dynamic influence of farm animals on soil density tends to become more severe as the grazing load per unit area and grazing intensity increase [82]. Our study found the density of pasture soil to increase to 1.40 g/cm 3 , or by 14.75%, compared to control (no grazing) and the soil to reach 3rd degree degradation by density increase in the variant of intensive agricultural grazing [83].…”
Section: Soil Quality Depending On the Methods Of Agricultural Grazin...mentioning
confidence: 53%